Pre-natal partner and pregnant woman in the state of Minas Gerais: an epidemiological study (Research, Society and Development, 2022)
The National Policy for Comprehensive Men's Health Care (PNAISH) instituted by Ordinance GM/MS No. 1944, of August 27, 2009, aims to expand access and acceptance of men through inclusion in the partner's prenatal care. This study aims to analyze the absolute frequency of men's participation in the partner's prenatal consultation, in addition to comparing the frequency of this with the pregnant woman's prenatal care, from 2018 to 2022, in the state of Minas Gerais, Brazil. This is a documentary study using a secondary data source, descriptive, exploratory, cross-sectional and retrospective, with a quantitative approach. Data were extracted from the database of the Department of Information and Informatics of the SUS (DATASUS). In which data were collected from the pregnant woman's prenatal consultations and the partner's prenatal care between January 2018 and September 2022 in the state of Minas Gerais, Brazil. In the spectrum analyzed, 2,379,931 prenatal consultations were reported in the State of Minas Gerais, 2,379,743 of which were for the pregnant woman's prenatal consultations and only 188 for the partner's prenatal consultations, demonstrating a very discrepant difference between prenatal care of the partner in relation to the pregnant woman, demonstrating a possible preoccupying situation for the trinomial.